Comparison Between Conditions of Major Roads Within and Outside the Port of Durban - Kunene, O. M.; Allopi, D. (Engineering, Technology & Applied Science Research, 2013)
Over the past years road traffic has increased at the Port of Durban. Due to the lack of maintenance, this has resulted in road deterioration. Roads are considered as the most important transport mode at the Port of Durban. It is an important mean for facilitating economic growth of local, regional and national industries. For the Port to maintain global competitiveness with the current trend of globalization, it has to be ensured that the roads are well maintained. The purpose of the paper is to provide an overview of road condition within and outside the Port. Verification and assessment of the condition of the existing eight major roads was conducted. Comparisons between the condition of the eight major roads within and outside the Port were highlighted. Conclusions and recommendations were also drawn based on the findings.